Asam lemak trans (trans-C18:1) dalam susu kambing - Andi Murlina Tasse; Rahim Aka (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
Trans fatty acid such as trans-octadecenoic acid (trans C18:1) in goat milk could be detected using silver-ion thin layer chromatography. Measurement of trans fatty acid content of goat milk derived from 8 Peranakan Etawah (PE) goats. The goats were divided into 2 groups in which group 1 was fed by elephant grass while group 2 was fed by native grass. The study showed that the proportion of trans fatty acid toward total fatty acid in group 1 and group 2 were 1.04% and 2.04% respectively. It was concluded that native grass could increase the proportion of trans fatty acid. Vaccenic acid trans-11 (C18:1) was the main content of trans fatty acid isomer in goat milk.   Key words : Trans fatty acid, Goat milk, PE